Antioxidant Activity and Bioactive Compounds of Fruits Available in Bangladesh - Monsur Ahmad; Farzana Shabnam Punam; Mahammad Amanullah; Nazmul Sarwar; Mohammad Mozibul Haque; Nilufa Yeasmin; Shireen Akther (Health Dynamics, 2024)
Background: The complex problems of different chronic degenerative diseases are spreading in human health across the globe. To combat this problem, fruits are the effective gear proved by many epidemiological studies. The aim of the study was to determine the antioxidant activity and three bioactive compounds like total flavonoids, total polyphenols and total anthocyanins in 23 species of fruits available in Bangladeshi market. Methods: Antioxidant activity (AOA) and bioactive compounds of fruits were determined by UV-visible spectroscopy. Antioxidant activity was undertaken by DPPH scavenging assay, total polyphenol content (TPC) was measured by folin-ciocalteu method and total flavonoid content (TFC) content was measured by aluminium chloride colorimetric method. Results: Among 23 species of fruits, AOA was higher in Katajamin (303 mg/100 g) followed by Dragon Fruits (171 mg/100 g), Guava (131 mg/100 g), Bael (130 mg/100 g) and average value was 125 mg/100 g of extract. TPC was varied from 10 to 305 mg GAE/100 g and average value was 87 mg GAE/100 g. Mango (305 mg GAE/100 g) showed higher TPC, followed by Pome Granate (222 mg GAE/100 g), Apple (207 mg GAE/100 g), Katajamin (141 mg GAE/100 g) and Bael (130 mg GAE/100 g). Again, TFC was ranged from Ashari (06±3.94 mg QE/g) to Tomato (84±13.69 mg QE/g) and the average TFC was 37 mg QE/g. In addition, total anthocyanin content (TAC) was highest in Mango (142±3.46 mg TA/100 g) and lower in Ashari (02±0.74 mg TA/100 g). There was a significant correlation (p≤0.05) between antioxidant activity and bioactive compounds and among the bioactive compounds. Conclusion: Important messages from this study are, majority of the rare fruits are the important sources of antioxidant and bioactive compounds which helps to reduce the risk of chronic degenerative diseases and can be used in food processing industry for nutraceutical product development.